Hyperimmune Targeting Staphylococcal Toxins Effectively Protect Against USA 300 MRSA Infection in Mouse Bacteremia and Pneumonia Models - Han, Xiaobing; Ortines, Roger; Mukherjee, Ipsita; Kanipakala, Tulasikumari; Kort, Thomas; Sherchand, Shardulendra P.; Liao, Grant; Mednikov, Mark; Chenine, Agnes L.; Aman, M. Javad; Nykiforuk, Cory L.; Adhikari, Rajan P. (Frontiers in Immunology, 2022)
Staphylococcus aureus has been acquiring multiple drug resistance and has evolved into superbugs such as Methicillin/Vancomycin-resistant S. aureus (MRSA/VRSA) and, consequently, is a major cause of nosocomial and community infections associated with high morbidity and mortality for which no FDA-approved vaccines or biotherapeutics are available. Previous efforts targeting the surface-associated antigens have failed in clinical testing. Here, we generated hyperimmune products from sera in rabbits against six major S. aureus toxins targeted by an experimental vaccine (IBT-V02) and demonstrated significant efficacy for an anti-virulence passive immunization strategy. Extensive in vitro binding and neutralizing titers were analyzed against six extracellular toxins from individual animal sera. All IBT-V02 immunized animals elicited the maximum immune response upon the first boost dose against all pore-forming vaccine components, while for superantigen (SAgs) components of the vaccine, second and third doses of a boost were needed to reach a plateau in binding and toxin neutralizing titers. Importantly, both anti-staphylococcus hyperimmune products consisting of full-length IgG (IBT-V02-IgG) purified from the pooled sera and de-speciated F(ab’)2 (IBT-V02-F(ab’)2) retained the binding and neutralizing titers against IBT-V02 target toxins. F(ab’)2 also exhibited cross-neutralization titers against three leukotoxins (HlgAB, HlgCB, and LukED) and four SAgs (SEC1, SED, SEK, and SEQ) which were not part of IBT-V02. F(ab’)2 also neutralized toxins in bacterial culture supernatant from major clinical strains of S. aureus. In vivo efficacy data generated in bacteremia and pneumonia models using USA300 S. aureus strain demonstrated dose-dependent protection by F(ab’)2. These efficacy data confirmed the staphylococcal toxins as viable targets and support the further development effort of hyperimmune products as a potential adjunctive therapy for emergency uses against life-threatening S. aureus infections.